The Design Diversity of Ornamental Earthenware towards the Craft Product Marketing in Bali on Global Era - Mudra, I Wayan (International Research Journal of Management, IT & Social Sciences, 2016)
Balis figure as a "living museum" culture of Hindu-Javanese was believed affecting the realization of Bali tourism development in this global era (Picard, 2006: 21-23). In term of this phenomenon, Bali was interesting by all parties for marketing the various craft products of non-Bali, unlike in Desa Kapal, Mengwi subdistrict, Badung regency, Bali province. The marketing invisible quantity was dominated by non-Bali ornamental earthenware. This dominance led to Balinese ornamental earthenware impressed simply seems "guests" in their own place. First, the research aims at finding out the design diversity of Balinese ornamental earthenware and non-Bali that was marketed in Desa Kapal. Second, the research was intended to know the sense that can be perceived behind the dominance of non-Bali ornamental earthenware designs. The relevance theory was used in analyzing was a semiotics by Roland Barthes (Zoest, 1993), the shape analysis theory (Vihma, 1990), and Derrida deconstruction method (Barker, 2014).